Decentralization and Institutional Development in Indonesia (A Literature Study) - Ananda, Candra Fajri (The International Journal of Accounting and Business Society, 2007)
Institutional development for better governance, to allow for better implementation of decentralization [included ï¬scal] and other policies, will take years, as unï¬nished if not decades, to complete. Such institutions must be built domestically, or even locally, they can not be imported from others. German experiences have shown how their adjustment efforts against the environment changes such as globalization, European Union, domestic inter-regional disparity reuniï¬cation) for a better quality of development. By analyzing some theories and comparison German and Indonesian experiences, there are three recommendations: (i) existing cultural context, (ii) inï¬‚uencing of changing role and relationship, and (iii) questions on timing and sequencing ofthe policy. These three institutional aspects should be considered in policy design at all level ofthe governments and need consequently a strong central government to lead and manage the process. Keywords: Decentralization, local institutions, comprehensive